Effect of Lambda Cyhalothrin on the Histoarchitecture of the Female Freshwater Catfish - Suman Gulati; M. Priyadarssini; E. Logeswari; R. Latha; K. Revathi (The Bioscan, 2025)
Pesticides are a crucial element in enhancing agricultural production. If the benefits of pesticides encompass their potential to boost economic prospects through augmented food and fiber production and reduction of vector-borne diseases, then the drawbacks entail significant health consequences for humans and the environment. Fishes play a significant role in aquaculture, serving as an excellent source of protein for humans. Today, the effect of pesticides on fish growth, survival, and reproduction is a significant concern due to their interference with normal physiological processes in these organisms. The application of pyrethroid insecticides for managing insect pests has risen dramatically. The excessive application of synthetic pyrethroids is speeding up environmental and water resource pollution, endangering aquatic organisms and posing an indirect threat to human life. Although pyrethroid compounds show much lower toxic effects on birds and mammals than organophosphates, numerous laboratory studies have shown their impact on arthropods and fish. The USEPA registered lambda cyhalothrin, a widely used agricultural pyrethroid, in 1988 is highly toxic to fishes and aquatic invertebrates. This study was aimed to evaluate histopathological findings of two distinct sub-lethal concentrations of lambda cyhalothrin on freshwater catfish. The liver, muscle, gills, ovary, brain, heart, thyroid, and head kidney (adrenal) tissues were preserved in 10% formalin for histopathological examination and showed marked pathological changes when compared to the control group of fishes.